The Years of Hunger: Soviet Agriculture, 1931–1933 - Davies, R. author. aut Link
XVII, 555 p.
Keywords: This book examines the Soviet agricultural crisis of 1931-1933 which culminated in the major famine of 1933. It is the first volume in English to make extensive use of Russian and Ukrainian central and local archives to assess the extent and causes of the famine. It reaches new conclusions on how far the famine was 'organized' or 'artificial', and compares it with other Russian and Soviet famines and with major twentieth century famines elsewhere. Against this background, it discusses the emergence of collective farming as an economic and social system.